1997
DOI: 10.1002/(sici)1097-461x(1997)64:2<183::aid-qua5>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Energies of dipole-bound anionic states

Abstract: Ž. Dipole-bound anionic states of CH CN, C H , and HF were studied using highly 3 3 2 2 correlated electronic structure methods and extended one-electron basis sets. The electron detachment energies were calculated using the coupled cluster method with single, double, and noniterative triple excitations. Geometrical relaxation of the molecular framework upon electron attachment and the difference in the harmonic zero-point vibrational energies between the neutral and the dipole-bound anionic species were calcu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
102
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 89 publications
(110 citation statements)
references
References 31 publications
8
102
0
Order By: Relevance
“…This stabilizing effect, caused by quantum mechanical charge fluctuations, is similar in magnitude to E bind KT , see Table 3. This finding is consistent with our earlier results for other dipole-bound anions 26,[31][32][33][34][35][36][37] and has important implications for designing model potentials to describe dipolebound anions and solvated electrons. 62,63 The value of ∆E bind MP2-disp increases from 370 cm -1 at the optimal geometry of the neutral to 382 cm -1 at the optimal geometry of the anion.…”
Section: Electron Binding Energiessupporting
confidence: 92%
See 2 more Smart Citations
“…This stabilizing effect, caused by quantum mechanical charge fluctuations, is similar in magnitude to E bind KT , see Table 3. This finding is consistent with our earlier results for other dipole-bound anions 26,[31][32][33][34][35][36][37] and has important implications for designing model potentials to describe dipolebound anions and solvated electrons. 62,63 The value of ∆E bind MP2-disp increases from 370 cm -1 at the optimal geometry of the neutral to 382 cm -1 at the optimal geometry of the anion.…”
Section: Electron Binding Energiessupporting
confidence: 92%
“…In fact, in many cases the electron binding energy of the dipole-bound anion has been dominated by the contribution from electron correlation. 26,[31][32][33][34][35][36][37][38] The very recent studies on dipole-bound anions of hydrogen-bonded clusters 39-41 and CH 3 NO 2 42 yielded similar conclusions.…”
Section: Hydrazine and Its Tautomermentioning
confidence: 86%
See 1 more Smart Citation
“…The binding of electrons to polar molecules has been addressed in many theoretical studies. [17][18][19][20][21][22][23][24][25][26][27][28][29][30] It has been shown that, within the Born-Oppenheimer (BO) approximation, species with a dipole moment greater than 1.625 D possess an infinite number of bound anionic states. 31,32 However, a more practical critical value to experimentally observe a dipole-bound state (DBS) of anion bound by at least 1 cm -1 was found to be slightly larger, ca.…”
Section: Binding Of An Excess Electron To Sodium Chloridementioning
confidence: 99%
“…In particular, the dispersion interaction of the excess electron with the electrons of the neutral parent molecule proved to be crucial for the stability of the dipole-bound anion 18,19,[21][22][23][24] although higher-order correlation effects can also be significant. [21][22][23][24]29,35 An excess electron may be trapped inside a molecular cluster instead of being attached to the dipole moment of the neutral cluster. The existence of such species, very often referred to as solVated electrons (SE), has been known since 1864 when they were observed in liquid ammonia.…”
Section: Binding Of An Excess Electron To Sodium Chloridementioning
confidence: 99%